Pengaruh Fraud Triangle terhadap Kemungkinan Kecurangan Pelaporan Keuangan Sektor Infrastruktur yang Terdaftar di Bursa Efek Indonesia Tahun 2020–2022 - Surenggono Surenggono; Lilik Mardiana (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
This research identifies four independent variables: external pressure (proxied by leverage), financial targets (proxied by ROA), supervisory ineffectiveness (proxied by BDOUT), and auditor turnover. The results of the analysis show that external pressure has a significant negative influence on financial statement fraud, where the higher the external pressure, the greater the possibility of fraud occurring. On the other hand, financial targets and supervisory ineffectiveness do not show a significant influence on financial statement fraud. Changing auditors also has no effect on fraud, because companies tend to change auditors to comply with regulations, not to avoid fraud detection. This research provides an important contribution to the understanding of the factors that influence financial statement fraud, as well as implications for management and supervisors to increase transparency and accountability in financial reports. Recommendations for further research include the use of qualitative methods and exploration of other variables that can influence financial statement fraud.